2005
DOI: 10.1590/s1677-55382005000200004
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneoscopy for treatment of renal and ureteral stones

Abstract: Retroperitoneoscopy is an effective, low-morbidity alternative for treatment of urinary stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 19 publications
3
22
0
6
Order By: Relevance
“…for laparoscopic pyelolithotomy. Soares et al [11] reported an operative time of 140 (66-260) minutes in their study. Adel Hunayun et al [16] reported an operative time of 112.1 minutes for laparoscopic pyelolithotomy in their study.…”
Section: Operative Timementioning
confidence: 83%
See 2 more Smart Citations
“…for laparoscopic pyelolithotomy. Soares et al [11] reported an operative time of 140 (66-260) minutes in their study. Adel Hunayun et al [16] reported an operative time of 112.1 minutes for laparoscopic pyelolithotomy in their study.…”
Section: Operative Timementioning
confidence: 83%
“…Similar results were reported by Goel et al [6] in their study, in which the hospital stay for laparoscopic pyelolithotomy patients was 3-4 days. Soares et al [11] reported that, in their study, the average hospital stay was 3 days (range 1-10) for laparoscopic pyelolithotomy patients.…”
Section: Hospital Staymentioning
confidence: 89%
See 1 more Smart Citation
“…However, these studies are inadequate, because they are nonrandomized and retrospective in nature; in these studies, either the stent has been used in all cases or has been used in the later half of the study after the initial few patients had prolonged drainage, or it was used to reduce the duration of drainage postoperatively in patients who had already undergone an operation [3,4,10].…”
Section: Discussionmentioning
confidence: 99%
“…In patients presenting with impacted large stones, particularly those located in the proximal ureter, open surgery provides the benefit of removing the stone in one procedure (1,2). the use of laparoscopy in the field of urology has progressed significantly in recent years.…”
mentioning
confidence: 99%